Movimiento de lesbianas, gays, bisexuales, transexuales en la construcción de políticas públicas de igualdad y no discriminación. La Libertad, 2018. - Zavaleta Urtecho, Lucyana Olenka (2019)
ABSTRACT The present investigation called “Movement of lesbians, gays, bixsexuals, transsexuals in the construction of public policies of equality and non-discrimination. La Libertad, 2018”, aims to describe the process of advocacy actions developed by the movement LGBT to build the regional public policy that promotes equality and non-discrimination based on sexual orientation and gender identity in the La Libertad Region, through Regional Ordinance No. 006-2014 - GR - LL / CR, promulgated in 2014. The ethnographic method has been used in order to describe and understand the beliefs, motivations, rules of coexistence, forms of organization and roles that the members of the LGBT movement of La Libertad fulfill. The case study method has also been used, which examines in various aspects each LGBT association from la Libertad. The data collection techniques were based on the group discussion with members of LGBT associations and in-depth interviews with the leaders of the LGBT movement, the members of the Regional Council and the technical representatives of the Regional Government civil servants, responsible for the implementation of the public policy. The aspects addressed throughout the investigation are described, from the collection and processing of the information to the discussion of the results. Within this framework, it is concluded that the LGBT movement has a significant impact on the construction of public policies that promotes equality and non-discrimination based on sexual orientation and gender identity, through the creation of alliances and the development of initiatives that strengthen in the degree of participation, cohesion and organization to achieve specific levels of representation and legitimacy, within civil society and state institutions